Sub-chronic Mptp-Induced Parkinsonism: Selective Sensitivity of the Balb/C Mice and the Prophylactic Roles of Nigella Sativa Oil - Folarin, Royhaan; Olonade, Akinola; Ogunkunle, Praise; Shallie, Philemon; Adenowo, Adenowo; Adeyanju, Muinat; Folarin, Paul; Amangele, Tarilayefa (My University, 2019)
Parkinsonism is a degenerative neurological syndrome characterised by dopamine deficiency in the basal ganglia. Despite ages of research, there is still lack of holistic and side-effect-free therapy for the disease. Nigella sativa is a multi-potent plant known for its historical and scientifically proven therapeutic potentials in the brain and other body organs. Despite the validity debates on the use of BALB/c mice strains in the modelling of Parkinsonism using MPTP, this study re-appraised the sensitivity versus resistance of the BALB/c mice strain to MPTP and further investigated the possible neuro-thrapeutic role of Nigella sativa oil (NSO) in the Parkinsonic endophenotypes elicited by MPTP in the BALB/c strain. Body weights, relative brain weights, striatal dopamine, striatal neuron density and recognition memory were studied in thirty-two (32) male albino mice, weighing between 18g -25g. They were divided equally into Control (administered with normal feed for 5 days), MPTP (administered with 18mg/kg MPTP i.p for 5 days), NS (administered with 1ml/kgbw NSO p.o. for 5 days), and NS+MPTP (administered with 1ml/kgbw NSO p.o. followed by 18mg/kg MPTP i.p for 5 days). Recognition memory was assayed through Novel Object Recognition test (NORT), and the animals were weighed and euthanised 24 hours after last administration. The brains were excised and the striatum assayed neurochemically for dopamine and illustrated histologically for neuronal density using the H&E stain. Parkinsonic traits such as mild tremor, significant down-regulation of dopamine and striatal neurons (p<0.05) were recorded in the BALB/c mice administered with MPTP only, confirming MPTP-sensitivity for these features. However, significant increase (p<0.05) in appetite, body weight, brain-body weight ratio, and recognition memory was also recorded in the MPTP-administered mice, though Nigella sativa was significantly prophylactic against the negative Parkinsonic features, and ‘moderative’ of the up-regulations induced by MPTP. While this suggests selective MPTP sensitivity and resistance in BALB/c strains, this study recommends the investigation of possible beneficial potentials of MPTP as observed. The research was conducted in conformance with the Animal Research Ethics Committee (AREC) guidelines of the Olabisi Onabanjo University.
Keywords: BALB/c; MPTP; Nigella sativa; Parkinsonism; Selectivity; Striatum